Cardiac contractility modulation for the treatment of moderate to severe HF. (2nd January 2021) - Rao, Ishu V.; Burkhoff, Daniel
ABSTRACT: Introduction : Heart failure (HF) affects over 6 million Americans and approximately 650, 000 new cases are diagnosed annually, with patients evenly split between HFrEF and HFpEF. Recent advances in therapy for these patients have been limited to pharmaceutical agents, with CRT remaining the most reliable device therapy option since its advent almost twenty years ago. In 2019, after almost two decades without the introduction of a new device therapy for the treatment of moderate HF, the FDA approved CCM® therapy, delivered by the Optimizer Smart device, for patients with NYHA Class III HF who are on guideline-directed medical therapy (GDMT), in normal sinus rhythm (NSR), and with EF ranging from 25% to 45%, and who are ineligible for CRT. Areas covered : Multiple clinical trials support the use of CCM to improve quality of life, functional class, and 6-min hall walk distance. This article will discuss the science behind CCM therapy, the presumed mechanisms of action, the pre-clinical studies that shaped subsequent endeavors, and the clinical trials that support its use. Expert opinion : The introduction of CCM therapy bridges a therapeutic gap for patients with few or no other therapeutic options for NYHA III heart failure.